Uniwersytecki wymiar kształcenia profesjonalnych służb społecznych w Polsce = University dimension of the education of professional social services in Poland - Żukiewicz, Arkadiusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Traditions of educating social services have been known in Poland since 1925 thanks to the efforts by Helena Radlińska and an association of the most outstanding theoreticians and practitians of social work of that time including; Marian Grotowski, Konstanty Krzeczkowski, Marian Godecki, Ludwik Krzywicki, Wacław Szubert, Kazimierz Korniłowicz, Czesław Babicki, Janusz Korczak, Jan Muszkowski, Faustyn Czerwijowski, Zygmunt Kobyliński, Maurycy Jaroszyński, Jan Strzelecki, Mieczysław Michałowicz, Józef Mikułowski-Pomorski, Władysław Radwan and Stanisław Rychliński, and many others.
Keywords: kształcenie uniwersyteckie; kształcenie pracowników; opieka społeczna